Towards the Use of Focus on Form Instruction in Foreign Language Learning and Teaching in Colombia - Macías, Diego Fernando (Íkala, Revista de Lenguaje y Cultura, 2011)
The present article seeks to encourage reflection on the meaning and potential of focus on form instruction as an alternative to improve the foreign language learning and teaching process of young and adult learners in Colombia. Initially, the concept and types of focus on form instruction are introduced, a brief rationale follows and findings from studies in this area are presented. Similarly, this manuscript discusses how this type of instruction might help students of English as a Foreign Language, especially young and adult learners, to communicate successfully as they gain knowledge of English linguistic forms. Finally, pedagogical implications are discussed and suggestions are offered regarding the use of focus on form instruction in the Colombian context.